THE SOVEREIGNTY, INDEPENDENCE AND FOOD SECURITY POST THE OMNIBUS LAW ON JOB CREATION - Suryani Suryani; Ari Handriatni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Food is the most important basic human need guaranteed in the 1945 Constitution of the Republic of Indonesia. The existence of the law on Job Creation will allegedly move Indonesia away from the goals of food sovereignty, independence and national food security. This research examines further the extent of legislation in the field of food and agriculture in order to realize food sovereignty, independence and food security as state goals. The research method used in this research is normative juridical research, namely research intended to study the application of rules or norms in positive law. The research approach used is a statutory approach. The results of this research are: 1) Food sovereignty, independence and food security as the embodiment of the constitutional mandate to achieve state goals, namely the welfare and prosperity of the people; 2) The existence of the Job Creation Law which encourages economic growth through easy investment policies to encourage the creation of jobs, has degraded food sovereignty and independence and placed greater emphasis on aspects of food security through food imports; 3) Control over the conversion of sustainable agricultural land and spatial planning policies as mandated by law is distorted by the presidential decree on national strategic projects which are hierarchically under the law